Parallel Training as a Way of Forming Students’ Profession-al Readiness - Кулаєва, З. А. (Міжнародний періодичний науковий журнал № 24, т. 2, грудень 2022, IndexCoper-nicuc, GooleScholar, 2022)
The system analysis of the learning process considers the problem of activating the activity of students in the educational process through programming, control of independent work and the creation of motivation through the professional specialization of training with the help of innovative technologies. Deactivation of these factors provokes information loss of the student at the initial stage of education. The learning model should be built taking into account external conditions that contribute to the development of the inclinations and traits of the individual into abilities and character, and then into skills and abilities, taking into account the resources of self-promotion to knowledge under the influence of emotions, will, motives, interests and personal needs of the student. When teaching in the mode of extracurricular learning activities, the teacher should take into account the personal characteristics of the student in order to maintain a positive motivational background and ensure the best result.
DOI: 10.30890/2567-5273.2022-24-02-008
Kulaeva Z. A. Parallel Training as a Way of Forming Students’ Professional Readiness / Z. A. Kulaeva // Modern engineering and innovative technologies: IndexCoper-nicuc, GooleScholar, 2022. - Issue 24. - Part 2. - P.72-78.
Keywords: Information losses; direct communication; differentiated learning; communicative mode; efficiency; critical thinking; assimilation of information; cognitive activity; extracurricular independent work ensure the best result